Spatial distribution of active and inactive rock glaciers and protalus ramparts in a sector of the Central Andes of Argentina ... : التوزيع المكاني للأنهار الجليدية الصخرية النشطة وغير النشطة وأسوار البروتالوس في قطاع من جبال الأنديز الوسطى في الأرجنتين ... - Cristian Daniel Villarroel; Ana Paula Forte (OpenAlex, 2020)
Rock glaciers and protalus ramparts are two of the main morphological features of the Central Andes in the Province of San Juan, Argentina. This sector of the Andes has one of the highest densities of occurrence of rock glaciers in the world. In this region, which has semiarid climatic characteristics, the presence of these landforms is important due to their solid state water reserves and as water resource regulators. Their occurrence is vital in several basins where, due to the lack of glaciers, debris-covered glaciers and perennial snow patches, rock glaciers are the only solid-state water reserves. However, the topo-climatic factors controlling the development and evolution of rock glaciers and protalus ramparts are not well known, which prevents an integrated management of the basins. This contribution, first, analyzes the spatial distribution of active and inactive rock glaciers and of protalus ramparts with respect to different topographic variables in the upper section of the Santa Cruz River basin. ... : الأنهار الجليدية الصخرية وأسوار البروتالوس هما من السمات المورفولوجية الرئيسية لجبال الأنديز الوسطى في مقاطعة سان خوان بالأرجنتين. يحتوي هذا القطاع من جبال الأنديز على واحدة من أعلى كثافات حدوث الأنهار الجليدية الصخرية في العالم. في هذه المنطقة، التي تتميز بخصائص مناخية شبه قاحلة، يعد وجود هذه التضاريس الأرضية مهمًا بسبب احتياطياتها المائية في الحالة الصلبة وكمنظمين للموارد المائية. حدوثها أمر حيوي في العديد من الأحواض حيث، بسبب نقص الأنهار الجليدية والأنهار الجليدية المغطاة بالحطام والبقع الثلجية الدائمة، الأنهار الجليدية الصخرية هي احتياطيات المياه الصلبة الوحيدة. ومع ذلك، فإن العوامل المناخية الطبوغرافية التي تتحكم في تطور وتطور الأنهار الجليدية الصخرية وأسوار البروتالوس ليست معروفة جيدًا، مما يمنع الإدارة المتكاملة للأحواض. تحلل هذه المساهمة، أولاً، التوزيع المكاني للأنهار الجليدية الصخرية النشطة وغير النشطة وأسوار البروتالوس فيما يتعلق بالمتغيرات الطبوغرافية المختلفة في القسم العلوي من حوض نهر سانتا كروز. في المجموع، تم جرد 375 شكلًا أرضيًا، منها 83 من الأنهار الجليدية الصخرية النشطة، و 81 غير نشطة و ...